THE INFLUENCE OF CULTURAL COMMUNICATION FACTORS ON ENGLISH COMMUNICATION IN AN INTERNATIONAL SERVICE INDUSTRY - Nualsri, Supawadee; Chaiya, Preeda (PEOPLE: International Journal of Social Sciences, 2016)
The main purpose of this study was to examine the relationship between cultural communication factors and English communication and to examine the influence of cultural factors on English communication in the service industry in Thailand. The sampling method was convenience sampling; 202 participants were randomly chosen by the human resource managers from the 10 international hotels participating in this study. As part of their jobs, the selected participants had to have contact with other international service industries or overseas branches and to communicate in English in various ways in their daily work routine. The research instrument was a questionnaire specifically designed to investigate the influence of cultural factors on English communication in the international service industry. The participants were asked to answer questions based on the concepts of body language, cultural awareness, cross-cultural communication, spoken communication, written communication, and nonverbal communication. The research findings can be summarized as follows:(1) cross-cultural communication factors were found to have an influence on English communication primarily whilst staff were using email, which was the most widely used form of communication in the industry; and (2) there were three cultural communication factors that affect English communication, which can be mapped into three significant groups: (a) body language, (b) cultural awareness, and (c) cross cultural communication.